New and emerging drug treatments for severe asthma. Issue 3 (13th February 2018) - Diver, S.; Russell, R. J.; Brightling, C. E.
Summary: Asthma is a common chronic inflammatory condition of the airways affecting over 300 million people world‐wide. In 5%‐10% of cases, it is severe, with disproportionate healthcare resource utilization including costs associated with frequent exacerbations and the long‐term health effects of systemic steroids. Characterization of inflammatory pathways in severe asthma has led to the development of targeted biological and small molecule therapies which aim to achieve disease control while minimizing corticosteroid‐associated morbidity. Herein, we review currently licensed agents and those in development, and speculate how drug therapy for severe asthma might evolve and impact on clinical outcomes in the near future.